2019
DOI: 10.1097/acm.0000000000002812
|View full text |Cite
|
Sign up to set email alerts
|

Alliance, Trust, and Loss: Experiences of Patients Cared for by Students in a Longitudinal Integrated Clerkship

Abstract: Interview protocol (English) Over the past year, we understand Medical Student X was involved in your care here with your primary care doctor, Dr. X, and may have seen you in other clinics or in the hospital as well. We know that you've had a long-standing and separate relationship with your primary care doctor, but we are specifically interested in how a student might add or take away from that relationship with your doctor. Can you tell me about a time working with student name during the last year? (quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(53 citation statements)
references
References 34 publications
0
53
0
Order By: Relevance
“…28 Other studies have shown how students from longitudinal integrated clerkships are seen by patients as critical member of their care team. 37 In our results, we found trainees were more likely to notice their value as doctors when they fulfill this role. They described, although in many cases implicitly, how this made them feel grateful and proud, enhancing their in-group experience.…”
Section: Discussionmentioning
confidence: 48%
“…28 Other studies have shown how students from longitudinal integrated clerkships are seen by patients as critical member of their care team. 37 In our results, we found trainees were more likely to notice their value as doctors when they fulfill this role. They described, although in many cases implicitly, how this made them feel grateful and proud, enhancing their in-group experience.…”
Section: Discussionmentioning
confidence: 48%
“…Twenty‐six studies were included 16,26,45–68 . LIC programmes at 16 institutions were described, representing six countries: Australia, Canada, South Africa, Taiwan, the United Kingdom and the United States.…”
Section: Resultsmentioning
confidence: 99%
“… Students bring efficiencies to consultations by completing histories and examinations for preceptors 50,67 Students bring thoroughness to consultations 49 and give attention and time to the patient 51,59,66 Students share patient information with healthcare professionals and across healthcare settings 45,49,51,59,64 Students support communication between healthcare professionals, 51,57,60 and healthcare settings 53 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal integrated clerkships (LICs) have been demonstrated to benefit students, [1][2][3] faculty, [4][5][6] patients, [7][8][9] communities, [10][11][12] and organizations, [13][14][15] yet understanding of why LICs work is limited. 16 Benefits include student engagement in advocacy, 17 preceptor satisfaction, 5 improved patient health, 7,18,19 and service provision. 13 A recent scoping review concluded LICs may confer benefits by facilitating student identity construction.…”
Section: Discussionmentioning
confidence: 99%